Comparison of clipping with and without epinephrine injection for the prevention of post‐polypectomy bleeding in pedunculated colon polyps. Issue 10 (October 2015) - Park, Yehyun; Jeon, Tae Joo; Park, Ji Young; Park, Soo Jung; Cheon, Jae Hee; Kim, Tae Il; Kim, Won Ho; Hong, Sung Pil
Abstract Background and Aim Post‐polypectomy bleeding (PPB) is the most common adverse event of colonoscopic polypectomy, especially in cases with large pedunculated polyps. To minimize the risk of PPB, several endoscopic preventive methods have been performed. The aim of this prospective, randomized study was to compare the rates of PPB following single (clipping alone) and combined (clipping plus epinephrine‐saline injection) methods in prevention of PPB in large pedunculated polyps. Methods Adult patients with pedunculated colorectal polyps with heads ≥ 10 mm were prospectively enrolled from March 2011 to January 2013. Patients were randomized to receive treatment of either clips alone (group A) or clips plus injection of epinephrine‐saline (group B) prior to a conventional polypectomy. PPB rate in both groups were compared. Results A total of 148 patients with 173 pedunculated colorectal polyps were enrolled. Groups A and B each had 74 patients, with 83 and 90 polyps, respectively. The mean head diameters were 17.2 ± 6.6 and 17.5 ± 6.7 mm in groups A and B, respectively (P = 0.748). Immediate PPB (IPPB) occurred in 10 cases (12.0%) from group A and 13 cases (14.4%) from group B (P = 0.64). There were no cases of delayed PPB or perforation. Multivariate analysis showed that inadequate bowel preparation and large head diameter of polyp were independent risk factors for IPPB. Conclusions The rate of IPPB is relatively high in cases with large pedunculated polyps, but these polyps can be successfully resected by snare polypectomy following use of the single prophylactic clipping method.